2000
DOI: 10.1037/0022-3514.79.4.602
|View full text |Cite
|
Sign up to set email alerts
|

Intergroup emotions: Explaining offensive action tendencies in an intergroup context.

Abstract: Three studies tested the idea that when social identity is salient, group-based appraisals elicit specific emotions and action tendencies toward out-groups. Participants' group memberships were made salient and the collective support apparently enjoyed by the in-group was measured or manipulated. The authors then measured anger and fear (Studies 1 and 2) and anger and contempt (Study 3), as well as the desire to move against or away from the out-group. Intergroup anger was distinct from intergroup fear, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

82
1,493
6
40

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,364 publications
(1,621 citation statements)
references
References 48 publications
82
1,493
6
40
Order By: Relevance
“…Moreover, our integrative model fit the data much better under in-group than under out-group disadvantaged conditions. These results lend support for our integrative approach in the sense that in-group disadvantage increased social identity salience, which is in line with IET's proposal that social identity salience sets the stage for group-based emotions, such as group-based anger, to occur (Mackie et al, 2000;E. R. Smith, 1993).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Moreover, our integrative model fit the data much better under in-group than under out-group disadvantaged conditions. These results lend support for our integrative approach in the sense that in-group disadvantage increased social identity salience, which is in line with IET's proposal that social identity salience sets the stage for group-based emotions, such as group-based anger, to occur (Mackie et al, 2000;E. R. Smith, 1993).…”
Section: Discussionsupporting
confidence: 85%
“…Indeed, our predictive model including the group efficacy pathway consistently fit better and explained more variance than an alternative model in which the group efficacy pathway to collective action was omitted. In other words, this integrative model adds value to models based on an intergroup emotion analysis alone (i.e., IET; Mackie et al, 2000;E. R. Smith, 1993), as well as providing more explanatory power than approaches focusing primarily on collective disadvantage and procedural unfairness associated with classic intergroup theories (e.g., SIT, RDT).…”
Section: Discussionmentioning
confidence: 98%
“…Mackie et al (2000) found that intergroup anger was distinct from intergroup fear, and the tendency to take action against the outgroup was distinct from the tendency to move away from the out-group. Lerner and Keltner (2001) found that anger (trait and state) related to favorable expectations, whereas fear related to unfavorable expectations.…”
Section: Personality Psychopathology and Perceptionsmentioning
confidence: 96%
“…The questionnaire was based on behavior reported by people with changes in appearance, considering that certain types of emotions give space to specific behaviors that may be offensive or not, i.e., the behavioral manifestation of stigma may differ depending on the type of emotion caused (14) . Stigmatizing behaviors that underlie the construction of the questionnaire were identified by the authors in the literature review and were organized into six categories: improper attention and stare, avoidance behavior, confuse behavior, rude and provocative behavior, bullying and external pressure to change their appearance (12) .…”
Section: Instrumentsmentioning
confidence: 99%